IMPLEMENTASI PENGAJARAN HIDUP BENAR MENURUT ROH KUDUS BERDASARKAN GALATIA 5:16-26 - Yehezkiel Sugeng Mulyono; Hana Suparti; Paulus Sentot Purwoko (Metanoia, 2022)
The teaching of righteous living according to the Holy Spirit is a life that is always receiving, filled and led by the Holy Spirit. In this sense, every believer must continue to live walking in the Holy Spirit. The Apostle Paul narrated his teaching to every believer in Galatians 5: 16-26 that every believer must give himself to live righteously according to the Holy Spirit. Because for the Apostle Paul, living rightly according to the Holy Spirit is living according to God's will and being able to practice the truth that has been revealed through Jesus Christ. Right living according to the Holy Spirit is defined by three theories. First, life receives holy spirit. Receiving the Holy Spirit absolutely, is also something that God promises to every believer. The presence of the Holy Spirit makes every believer live in Him, which then guides the believer to become true disciples of Christ, and can also live to produce the fruit of the Holy Spirit which is the hallmark of the believer's life. Second, Life Produces the fruit of the Holy Spirit. From the fruit you know the tree, the fruit is the natural flow of the divine nature through the human being created, the fruit of the holy Spirit is the greatest and highest expression of human character and culture as a believer. The fruit of the Holy Spirit is also the fulfillment of salvation that will reach glorious perfection. Third, life belongs to Christ. Christ's is a believer whose life is always led by the Holy Spirit, will produce divine attributes as advised by the Apostle Paul in (Galatians 5: 22-23).